Influence of Different Drying Methods on Aroma Compounds in Hami-Melon Using Headspace Solid Phase Micro Extraction - Bi, Jin-Feng; Bai, Sha-Sha; Wang, Pei (Asian Journal of Chemistry, 2011)
This study aimed to analyze the influence of three different drying methods on aroma compounds in hami-melon and explore the optimal drying method for hami-melon. Headspace solid phase micro extraction coupled with gas chromatography-mass spectrometry (GC-MS) was used to identify the aroma compounds in the dehydrated hami melon samples by hot air drying, vacuumfreezing drying and explosion puffing drying. The experimental results showed that (1) aroma compounds in fresh samples mainly consist of esters (14.3 %), alcohols (43.9 %), aldehydes (27.1 %) and acids; (2) the content of the aroma compounds in the dehydrated samples changed due to the drying treatment; (3) much ketones were produced in the samples dehydrated by hot air drying and made them taste like being cooked; (4) more acids were produced and the great loss of alcohols happened in the samples dehydrated by vacuum-freezing drying and the flavour of these samples changed significantly; (5) most of hami-melon special aroma compounds remained in the samples treated by explosion puffing drying, including ethanol, 3-nonen-1-ol, ene aldehydes and so on. It was obviously that different drying methods had significantly impact on the aroma compounds of the hami melon. Due to the great loss of hami-melon special aroma compounds in the processing of hot air drying and vacuum-freezing drying, the explosion puffing drying was the optimal drying method for hami melon.